RETRACTED: The Role of Customer Satisfaction in Mediating The Effect of Service Quality and Price Perception on Word of Mouth - Hidayatun Ni’mah; elwisam elwisam; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to analyze the Role of Customer Satisfaction in mediating the influence of Service Quality and Price Perception on Word of Mouth in Central Travels Jakarta. This study used primary data by distributing questionnaires as many as 100 respondents. The data were analyzed using Structural Equation Modeling analysis using AMOS version 22 program. Based on the results of the study, it shows that the variables of Service Quality and Price Perception not only directly affect Word of Mouth, but Service Quality and Price Perception also affect indirectly.